2006
DOI: 10.3126/jiaas.v27i0.702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climate Change and CO<sub>2</sub> Concentration on Growth and Yield of Rice and Wheat in Punjab: Simulations Using CSM-CERES-Rice and CSM-CERES-Wheat Models

Abstract: Recent trends of a decline or stagnation in the yield of rice and wheat in rice-wheat (RW) systems of the Indo-Gangetic Plains (IGP) have raised serious concerns about the regional food security. The effect of future climate change on crop production adds to this complex problem. The validated CSM-CERES-Rice and CSM-CERES-Wheat (Ver. 4.0) data were used to test the sensitivity of the models in Punjab, India. The models were sensitive to climatic parameters (temperature, CO2 concentration, solar radiation and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Temperature primarily affected growth duration with lower temperature increasing the length of time that the crop could intercept radiation. Amgain et al (2006) reported that increase in minimum and maximum temperature by 4 0 C over the base scenario decreased the wheat yield by 4%. Reduction of minimum and maximum temperature by 4 0 C and increase in CO 2 by 20 ppm showed increase in yield (Amgain, 2004).…”
Section: Simulations Of Csm-ceres-wheat Model To Climate Change Parammentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature primarily affected growth duration with lower temperature increasing the length of time that the crop could intercept radiation. Amgain et al (2006) reported that increase in minimum and maximum temperature by 4 0 C over the base scenario decreased the wheat yield by 4%. Reduction of minimum and maximum temperature by 4 0 C and increase in CO 2 by 20 ppm showed increase in yield (Amgain, 2004).…”
Section: Simulations Of Csm-ceres-wheat Model To Climate Change Parammentioning
confidence: 99%
“…Climate change via increasing atmospheric CO 2 concentration can affect global agricultural production through changes in photosynthesis and transpiration rates for examples the beneficial effect of 700 ppm CO 2 would be nullified by an increase of only 0.9 0 C in temperature (Chatterjee et al, 2003). Although the solar radiation received at the surface will be variable geographically, on an average it is expected to decrease by about 1% (Hume & Cattle, 1990;Pathak et al, 2004;Amgain et al, 2006). Various studies have reported the marked effects of climate change more in rice and wheat yield because of its photo-respiration cycle (Timsina & Humphreys, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temperature increase will alter the timing and amount of rainfall. Increments in both maximum and minimum temperature by 4°C decreased rice yield by 34% as compared to base scenario with current weather data (Amgain et al, 2006). The Indian economy largely depends on agriculture which is highly influenced by the spatio-temporal variability of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Its components (temperature, solar radiation, rainfall, relative humidity and wind velocity) independently or in combination, can influence crop growth and productivity (Amgain et al, 2006).…”
Section: Introductionmentioning
confidence: 99%